Characterization of Phytophthora infestans population in potato crop from Tarai regions of Uttarakhand in India - TOUSEEF HUSSAIN, B.P. SINGH, S.K. KAUSHIK; V.S. PUNDHIR, MEHI LAL*, SAURABH YADAV, ANUBHA GUPTA (Indian Phytopathology, 2016)
Phytophthora infestans (Mont.) de Bary is a threat for potato cultivation in India including in tarai regions. A total of 42 isolates of P. infestans were collected from different districts of Uttarakhand during 2007-14 and diversity analysis was performed using biological and molecular markers. Using biological markers, both A1 and A2 mating type & metalaxyl sensitivity was observed up to 200 ppm. Eight to eleven gene complexes were observed. Using molecular markers, mt haplotypes results revealed that cent–percent isolates belonged to a new population (Ia mt haplotype). Simple Sequence Repeats markers revealed that P. infestans population having two to three alleles with Pio-4 primer and one to two alleles with Pinf SSR1 primer. The results of the present study revealed that increased tolerance to metalaxyl, most complex races and new population. This new population is more aggressive, complex and hence this will require new management strategies to control the disease.